2019
DOI: 10.1136/bmjopen-2018-026186
|View full text |Cite
|
Sign up to set email alerts
|

Productivity loss due to menstruation-related symptoms: a nationwide cross-sectional survey among 32 748 women

Abstract: ObjectiveTo evaluate age-dependent productivity loss caused by menstruation-related symptoms, measured in absenteeism (time away from work or school) and presenteeism (productivity loss while present at work or school).MethodsDesign/setting: internet-based, cross-sectional survey conducted in the Netherlands from July to October 2017.Participants: 32 748 women aged 15–45 years, recruited through social media.Outcome measures: self-reported lost productivity in days, divided into absenteeism and presenteeism; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
139
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 35 publications
(44 reference statements)
15
139
0
4
Order By: Relevance
“…The high rate of absenteeism identified during menstruation among female university students in this study is in line with previous reports conducted in other countries (although slightly higher), as analyzed in a systematic review and meta-analysis by Armour et al [10]. Absenteeism rates were higher when associated with greater scores on the VAS scale for dysmenorrhea, these data are in agreement with former studies conducted in the Netherlands by Schoep et al, Femi Agboola et al in Nigeria, and in Sri Lanka by Hapuarachchige et al [24][25][26]. The high rates of absenteeism associated with dysmenorrhea and to an elevated intensity of menstrual pain could be related to an incorrect management of menstruation in Spain.…”
Section: Discussionsupporting
confidence: 93%
“…The high rate of absenteeism identified during menstruation among female university students in this study is in line with previous reports conducted in other countries (although slightly higher), as analyzed in a systematic review and meta-analysis by Armour et al [10]. Absenteeism rates were higher when associated with greater scores on the VAS scale for dysmenorrhea, these data are in agreement with former studies conducted in the Netherlands by Schoep et al, Femi Agboola et al in Nigeria, and in Sri Lanka by Hapuarachchige et al [24][25][26]. The high rates of absenteeism associated with dysmenorrhea and to an elevated intensity of menstrual pain could be related to an incorrect management of menstruation in Spain.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, on the other side, respondents were themselves not willing to be physically active and have confessed to rather have rest during menstruation. Schoep et al (2019) have reported 80% presenteeism during menstruation among their sample of 32,748 women in Netherlands where 'presenteeism' denotes loss of productivity while present at work or school while MRSs were responsible for 24% of total absenteeism for working women and students. A similar study was conducted in London by Bruinvels, Burden, Brown, Richards & Pedlar (as cited in Joseph, 2016) among Elite and Non-Elite Athletes in 2015, which covered 789 participants through an online survey and 1073 face to face interviews.…”
Section: Resultsmentioning
confidence: 99%
“…Taylor, as cited in Joseph 2016). Schoep et al (2019) stated that the impact of MRSs on women should be focussed upon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations